Clinical study of typhoid ileal perforation and determination of preferred operative procedure in its management in Gandhi medical college and associated Hamidia hospital of Madhya Pradesh, India - Jain, Sandeep; Patbamniya, Naveen Kumar; Kanwar, Krishna; Damor, Mahendra (International Surgery Journal, 2017)
Background: To analyze clinical and operative findings in typhoid ileal perforation and determining preferred operative procedure. Methods: All clinically suspected typhoid ileal perforation is classified into three categories depending on history, clinical and intraoperative findings (CAT I, CAT II, CAT III). All patients undergone surgical repair. Patient outcome in terms of complications, morbidity and mortality were compared to define the best procedure for Typhoid ileal perforation Results: Out of 105 patients, majorities were less than 30 years and were males (4:1). Most common presentation being pain abdomen (100%), followed by fever (85.71%) while signs of peritonitis are present in all patients (100%) and majority patients had septicemia (77.14%) (TLC count >11,000 or <4,000) on presentation. 82 (78.09%) patients were Widal positive. Among CAT I (n=47), majority require primary repair (n=27; 57.44%) followed by resection anastomosis (n=14; 29.78%) and ileostomy (n=5; 10.63%) while among CAT II (n=38), majority require ileostomy (n=12; 31.57%) followed by resection anastomosis (n=5; 13.5%), whereas in CAT III (n=20), most patients require Ileostomy (n=14; 70%). Overall complications are more with CAT III (n=12; 60%) compared to CAT I (n=08; 17%) and CAT II (n=10; 26.31%) (p<0.001). Wound infection being most common complication (n=24; 22.85%), while fecal fistula more common with resection anastomosis (n=5; 21.73%) followed by primary repair (n=7; 14.89%). Mortality maximum with CAT III patients (n=6; 30%) (p<0.05). Stoma related complications mostly seen in CAT III. Among CAT II, two patients (5.2%) develop intra-abdominal abscess and two patients (5.2%) undergone stoma revision. Conclusions: Primary repair and resection anastomosis are safer in CAT I while ileostomy is safer surgery in CAT III and CAT II. Resection anastomosis should be avoided in higher categories in fear of fecal fistula and related complications.